Insulin Secretion and Interleukin-1β Dependent Mechanisms in Human Diabetes Remission After Metabolic Surgery - Chen, Chih-Yen; Lee, Wei-Jei; Asakawa, A.; Fujitsuka, N.; Chong, Keong; Chen, Shu-Chun; Lee, Shou-Dong; Inui, A. (Current Medicinal Chemistry, 2013)
To compare endocrine, metabolic, and inflammatory changes induced by gastric bypass (GB) and sleeve gastrectomy (SG) in patients with type 2 diabetes mellitus (T2DM), and to investigate the mechanisms of success after metabolic surgery. Sixteen GB and 16 SG patients were followed up before and at 1 year after surgery. The 75-g oral glucose tolerance test (OGTT) was performed before and after surgery. Glucose homeostasis, serum interleukin-1β, plasma gut hormones and adipokines, and the United Kingdom Prospective Diabetes Study (UKPDS) ten-year cardiovascular risks were evaluated. The diabetes remission rate was significantly higher in GB than SG. Changes in the area under the curve (AUC) for glucose were greater in those with complete and partial remission after GB and remitters after SG than non-remitters after SG, whereas changes in AUC for C-peptide were higher in complete and partial remitters after GB than non-remitters after SG. Insulinogenic index was enhanced and serum interleukin-1β was reduced in complete remitters after GB and remitters after SG. Logistic regression analysis confirmed that insulinogenic index and interleukin-1β, not insulin resistance, were the factors determining the success of diabetes remission after metabolic surgeries. GB and SG significantly reduced the ten-year risk of coronary heart disease and fatal coronary heart disease in T2DM patients after surgery, while GB had the additional benefit of reduced stroke risk. Human diabetes remission after metabolic surgery is through insulin secretion and interleukin-1β dependent mechanisms. GB is superior to SG in cardiocerebral risk reduction in Asian non-morbidly obese, not well-controlled T2DM patients.
Keywords: Cardiovascular risk